Interventions for African pastoral development under adverse production trends - International Livestock Centre for Africa (International Livestock Centre for Africa, 1988)
Reviews the characteristics of African pastoralism. Describes the major technical land institutional interventions along with the reasons why they have proved so difficult. The technical interventions include water development breed improvement, grazing blocks,range management, veterinary campaigns, tick control, fodder banks, grazing cells, abattoirs and introduction of camels & goats, and the institutional interventions include group ranches, parasatal ranches, fattening programs, service centres & barefoot veterinairians, herders' associations, mobile extension units, restocking projects, sedentarization, irrigation and water harvesting.